Direction-dependent system modeling approaches exemplified through an electronic nose system - Rosenqvist, F.; Ai Hui, Tan; Godfrey, K.; Karlstrom, A. (2006)
The modeling of processes exhibiting direction-dependent behavior is considered. Depending on the application, different models may be suitable. This brief is concerned with the use of Wiener models and piecewise-linear (PWL) models. These approaches are applied to data from an electronic nose system, for which knowledge of the physical principles is combined with system identification methods. Both models are found to provide close approximations to the behavior of the system itself.